175k views
3 votes
Please help please I don’t know :( explain please

Please help please I don’t know :( explain please-example-1

2 Answers

5 votes

Answer:

t = 5

Explanation:

h(t) = -10t + 6

After that you just write -10t + 6 = -44

Subtract 6 from -44

-44 - 6 = -50

So you will have

-10t = -50

Then you do -10t/-10 = -50/-10

-10t/-10 = t

-50/-10 = 5

So the final answer is t = 5

For proof, plug 5 in.

-10(5) + 6 = ?

-10(5) = -50

-50 + 6 = -44

SO THIS IS THE CORRECT ANSWER LEZZGO!

User Syed Aslam
by
5.4k points
4 votes

Answer:

t = 5

Explanation:

It's asking what t needs to equal for the equation to be equivalent to -44.

-10t + 6 = -44

-10t = -50

t = 5

check

-10(5) + 6 = -44

-50 + 6 = -44

-44 = -44

User Bnabilos
by
6.2k points